Student Movement (Study of the Role of Trisakti University Students in May 1998 in the Process of Substitution of New Order Power) - Siti Jubaedah (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2019)
The tragedy of the shooting of Trisakti students on Tuesday, May 12, 1998, then the killing of four students in the campus area made the entire campus community grieve and caused public outrage, so that not only the small community, but all of Indonesia demanded President Soeharto's resignation from leadership for 32 years has occupied. Massive demonstrations were taking place everywhere. Many students then came to Jakarta to call for the same demands. Until the occupation of the DPR / MPR RI building by students from various campuses. Seeing the increasing demands for resignation, President Soeharto at a meeting at the Presidential Palace said he refused to stop. However, with increasing demands from all over the country the resignation of President Soeharto, finally on May 21, 1998, it stopped, eight days after the Trisakti Tragedy. So great was the influence of the Trisakti Student Movement that Suharto laid down the position he had occupied for 32 years. The impact of the Trisakti Student Movement did not end there, changes in all fields of both social and government are the biggest impact of the 1998 Trisakti Student Movement. But the Trisakti Tragedy still leaves homework for us all. The investigation of the Trisakti case has not yet been completed and the party responsible for the case has not yet been tried. However, this will not stop Indonesian students from striving to call for the voice of the people.